Ultrasound assessment of gastric content in the immediate postpartum period: a prospective observational descriptive study. Issue 7 (26th June 2017) - Vial, F.; Hime, N.; Feugeas, J.; Thilly, N.; Guerci, P.; Bouaziz, H.
Abstract : Introduction: Pulmonary aspiration of gastric contents in pregnant women undergoing general anesthesia or sedation/analgesia in the peripartum period is a feared complication in obstetric anesthesia. We assessed the changes in antral cross‐sectional area (CSA) with ultrasonography in laboring women and in the immediate postpartum period. Patients and methods: In an observational study in a university‐affiliated maternity, gastric ultrasonography examinations were performed in non‐consecutive laboring women, after epidural analgesia insertion and after childbirth. Assessment of antral CSA, difficulty of performance on a numerical scale, and factors that could influence gastric content were noted. A cut‐off value of 381 mm 2 was taken for the diagnosis of empty stomach. Results: One hundred women were enrolled in the study. Median antral CSA was 469 mm 2 [25th–75th] [324–591] after epidural insertion and 427 mm 2 [316–574] after delivery. Antral CSA was ≥ 381 mm 2 in 59 of 90 women (65%) after epidural insertion vs. 48 of 100 women (48%) after delivery ( P  = 0.59). Median variation of antral CSA between two measurements was 36 mm 2 [−42 to 114]. Gastric ultrasonography was significantly more difficult to perform during labor than immediately post‐delivery (median difficulty score 5 [2–7] vs. 2 [1–4], P  < 0.0001). No risk factors (pain, anxiety, diabetes, smoking) were significantly associated with the occurrence of full stomach post‐delivery. Conclusion: This study demonstrated that 48% of parturients in the immediate postpartum period presented an antral CSA ≥ 381 mm 2, cut‐off being accepted for diagnosis of empty stomach and emphasizes the need for re‐assessing before any general anesthetic procedure.